Second Copy of Suma Evangelijų from the First Edition of Knygos Nobažnystės (1653) - Šinkūnas, Mindaugas; Šinkūnas, Mindaugas (Knygotyra, 2021)
It has long been thought that the only known 1653 copy of the first edition of the Knygos Nobažnystės is preserved in Sweden. The sammelband consists of a hymnal without a separate title page, the postil “Suma Evangelijų”, and the prayer book “Maldos krikščioniškos” with the catechism Katekizmas arba trumpas pamokslas. One part (the postil “Suma Evangelijų”) of the Knygos nobažnystės is preserved in the library of the Emeryk Hutten-Czapski National Museum in Kraków. It has hitherto been classified by bibliographers as a counterfeit edition, but a comparative analysis leaves no doubt that it is the second known copy of the first edition of the Knygos Nobažnystės postil “Suma Evangelijų”.
Keywords: “Knyga nobažnystės”; “Suma Evangelijų”; counterfeit; bibliography; provenance; Marcjan Zabiełło